Impacts of deep boundary layer on near-surface ozone concentration over the Tibetan Plateau. (1st February 2023) - Chou, Yan; Huang, Qian; Zhang, Yongpeng; Luo, Jiali; Wang, Mengyuan; Liao, Huiren; Zhang, Yunshuai; Bai, Zhixuan
Abstract: The deep atmospheric boundary layer in winter and spring over the Tibetan Plateau (TP) facilitates the exchange of mass and chemical species between the troposphere and stratosphere. Using ERA5 reanalysis data (1979–2018), this paper analyzes the atmospheric process over the TP when the dynamical tropopause (1.5 PVU surface) approaches the top of the deep boundary layer, which would affect the concentration of near-surface ozone. The result shows that the near-surface (at the height about 500–550 hPa) ozone concentration increases when the tropopause descends and adjoins the top of the deep boundary layer. The influence mechanism of the deep boundary layer on the increase of surface ozone on February 27, 2008 is studied by the WRF-Chem model. It is found that the calculated (using Reynolds average method) near-surface ozone increases by about 8 ppb per hour due to the vertical transport when the ozone-rich air from the stratosphere penetrates into the troposphere. Furthermore, a large eddy simulation (LEM model) is used to investigate the turbulence structure and development during the formation of the deep atmospheric boundary layer in the same case. It is found that a separate weak-turbulence layer forms at the height of about 6000 m AGL at 1300 LT below the tropopause fold. The upper-level turbulence couples with the boundary-layer turbulence after 1900 LT. As a result, the strong boundary layer turbulence causes the ozone-rich air from the stratosphere to mix with air near the surface layer. Highlights: The increase of the near-surface ozone caused by turbulence transport over the Tibetan Plateau was investigated. A separate weak-turbulence layer is formed under the tropopause folding due to the large wind shear. Turbulence coupling occurs when the dynamical tropopause approaches the top of the deep boundary layer. Enhanced boundary-layer turbulence mixes the ozone-rich air from the stratosphere to near the surface layer.